Language and linguisticality in Gadamer's hermeneutics - Schmidt, Lawrence K. (Lanham Lexington Books, 2000)
In this book, internationally recognized scholars in philosophical hermeneutics discuss various aspects of language and linguisticality. The translations of Hans-Georg Gadamer's two recent essays provoke a preliminary discussion on the philosopher's polemic claim in Truth and Method"Being that can be understood is language." Topics addressed by the contributors include the relationship of rituals to tradition and the immemorial; the unity of the word; conversation; translation and conceptuality; and the interrelationship between the art of writing and linguisticality. This work is of critical importance to anyone interested in Gadamer's claims regarding the boundaries of language, the transition from the prelinguistic to linguistic realms, and the role of rituals in this transition.